The morphology and histology of the genital system of Trigonephrus gypsinus and Trigonephrus latezonatus (Gastropoda: Pulmonata) - Brinders, E. M.(Elizabeth Maria) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1989.